Các yếu tố đóng góp vào tăng trưởng kinh tế thành phố Hồ Chí Minh - Nguyễn Thị, Cảnh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
This study incorporates both qualitative and quantitative approaches using Solow model combined with I/O tables to determine contributory factors to economic growth of Ho Chi Minh City (HCMC) during the past periods (2006-2010 and 2011-2015). The findings suggest that the HCMC economy occupies a major role in the national economy in terms of its size and high growth rates. The quality of economic growth, despite a drop in the 2011-2015 growth rate, has improved, which is significantly contributed by capital. While there is greater contribution of its total factor productivity (TFP) to growth during the later period, the factor of labor is recorded with decreasing contribution levels; this also implies an enhancement in the growth quality. The study, accordingly, proposes several recommendations for accelerating the city's growth over the coming terms
Keywords: HCMC economy; contributory factors to growth; I/O table; TFP